2022
DOI: 10.1159/000525375
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase-2 from Cancer Associated Fibroblasts: An Environmental Target for Hepatocellular Carcinoma?

Abstract: Introduction: Heparin sulfate proteoglycans in the liver tumour microenvironment (TME) are key regulators of cell signaling, modulated by Sulfatase-2 (SULF2). SULF2 overexpression occurs in hepatocellular carcinoma (HCC). Our aims were to define the nature and impact of SULF2 in the HCC TME. Methods: In liver biopsies from 60 patients with HCC, expression and localisation of SULF2 was analysed associated with clinical parameters and outcome. Functional and mechanistic impacts were assessed with immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Sulfatase overexpression is related to more advanced diseases and worse patient outcomes in a number of cancers. Furthermore, Sulfatase overexpression occurs in hepatocellular carcinoma (HCC) [45] . Sulfatase promotes breast cancer progression and regulates the expression of tumor‐related genes in breast cancer [46] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfatase overexpression is related to more advanced diseases and worse patient outcomes in a number of cancers. Furthermore, Sulfatase overexpression occurs in hepatocellular carcinoma (HCC) [45] . Sulfatase promotes breast cancer progression and regulates the expression of tumor‐related genes in breast cancer [46] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Sulfatase overexpression occurs in hepatocellular carcinoma (HCC). [45] Sulfatase promotes breast cancer progression and regulates the expression of tumor-related genes in breast cancer. [46] A novel treatment for postmenopausal women with hormone-dependent breast cancer is the development of steroid sulfatase inhibitors.…”
Section: Real-time Polymerase Chain Reaction Analysis Of Caspase-3 An...mentioning
confidence: 99%
“…SULF2 is also related to ECM remodeling. For example, the cancer associated fibroblasts of HCC could release stromal SULF2 into ECM, which could influence the modification of GPC3 in ECM and promote HCC metastasis by activating downstream molecules like β-catenin, STAT3 and NF-κB [114]. Furthermore, researchers indicated that high expression of SULF2 in hepatic stellate cells could increase the levels of collagen I and α-SMA, thereby promoting liver fibrosis, which is an important risk factor for HCC [115].…”
Section: Sulfs Regulate Tumor Metastasis By Reprogramming Tmementioning
confidence: 99%
“…The drug resistance mechanisms have hindered the efficacy of sorafenib, and sorafenib monotherapy only brings a survival benefit of about two months for the advanced liver cancer patients. [3,[6][7][8] Recently, it is demonstrated that sorafenib could also induce ferroptosis, [9] an iron-dependent programmed cell death that occurs primarily through excessive peroxidation of polyunsaturated fatty acids (PUFAs). Sorafenib induces GSH depletion and glutathione peroxidase 4 (GPX4) inactivation by inhibiting the function of cystine glutamate transporter (system x c − ), ultimately leading to lipid peroxide accumulation and triggering ferroptosis.…”
Section: Introductionmentioning
confidence: 99%